Molecular Imaging Visualizes Recruitment of Inflammatory Monocytes and Macrophages to the Injured Heart - Heo, Gyu Seong; Kopecky, Benjamin; Sultan, Deborah; Ou, Monica; Feng, Guoshuai; Bajpai, Geetika; Zhang, Xiaohui; Luehmann, Hannah; Detering, Lisa; Su, Yi; Leuschner, Florian; Combadière, Christophe; et al. (Circulation research, 2019)
RATIONALE:Paradigm shifting studies have revealed that the heart contains functionally diverse populations of macrophages derived from distinct embryonic and adult hematopoietic progenitors. Under steady-state conditions, the heart is largely populated by CCR2− (C-C chemokine receptor type 2) macrophages of embryonic descent. After tissue injury, a dramatic shift in macrophage composition occurs whereby CCR2+ monocytes are recruited to the heart and differentiate into inflammatory CCR2+ macrophages that contribute to heart failure progression. Currently, there are no techniques to noninvasively detect CCR2+ monocyte recruitment into the heart and thus identify patients who may be candidates for immunomodulatory therapy. OBJECTIVE:To develop a noninvasive molecular imaging strategy with high sensitivity and specificity to visualize inflammatory monocyte and macrophage accumulation in the heart. METHODS AND RESULTS:We synthesized and tested the performance of a positron emission tomography radiotracer (Ga-DOTA [1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid]-ECL1i [extracellular loop 1 inverso]) that allosterically binds to CCR2. In naive mice, the radiotracer was quickly cleared from the blood and displayed minimal retention in major organs. In contrast, biodistribution and positron emission tomography demonstrated strong myocardial tracer uptake in 2 models of cardiac injury (diphtheria toxin induced cardiomyocyte ablation and reperfused myocardial infarction). Ga-DOTA-ECL1i signal localized to sites of tissue injury and was independent of blood pool activity as assessed by quantitative positron emission tomography and ex vivo autoradiography. Ga-DOTA-ECL1i uptake was associated with CCR2+ monocyte and CCR2+ macrophage infiltration into the heart and was abrogated in CCR2 mice, demonstrating target specificity. Autoradiography demonstrated that Ga-DOTA-ECL1i specifically binds human heart failure specimens and with signal intensity associated with CCR2+ macrophage abundance. CONCLUSIONS:These findings demonstrate the sensitivity and specificity of Ga-DOTA-ECL1i in the mouse heart and highlight the translational potential of this agent to noninvasively visualize CCR2+ monocyte recruitment and inflammatory macrophage accumulation in patients.